2018
DOI: 10.1161/circulationaha.117.027451
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Impaired Parasympathetic Activity to Right Ventricular Dysfunction and Pulmonary Vascular Remodeling in Pulmonary Arterial Hypertension

Abstract: RV dysfunction is associated with reduced systemic parasympathetic activity in patients with PAH, with an inadequate adaptive response of the cholinergic system in the RV. Enhancing parasympathetic activity by PYR improved survival, RV function, and pulmonary vascular remodeling in experimental PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
90
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 48 publications
15
90
1
1
Order By: Relevance
“…Several investigators have demonstrated an autonomic imbalance in PAH (Lima-Seolin et al, 2017;Rigatto, Casali, Shenoy, Katovich, & Raizada, 2013;Wensel et al, 2009). Various reports have indicated the efficacy of autonomic modulatory therapies, such as pulmonary arterial denervation, -blocker and acetylcholine esterase inhibitor (Bogaard et al, 2010;Chen et al, 2013;da Silva Gonçalves Bós et al, 2018). We also have shown the impairment of baroreflex function in the present study by identifying the characteristics of baroreflex subsystems and the total arc in rats with MCT-induced PAH.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Several investigators have demonstrated an autonomic imbalance in PAH (Lima-Seolin et al, 2017;Rigatto, Casali, Shenoy, Katovich, & Raizada, 2013;Wensel et al, 2009). Various reports have indicated the efficacy of autonomic modulatory therapies, such as pulmonary arterial denervation, -blocker and acetylcholine esterase inhibitor (Bogaard et al, 2010;Chen et al, 2013;da Silva Gonçalves Bós et al, 2018). We also have shown the impairment of baroreflex function in the present study by identifying the characteristics of baroreflex subsystems and the total arc in rats with MCT-induced PAH.…”
Section: Discussionsupporting
confidence: 66%
“…They also reported that the baroreflex dynamic function does not change significantly in spontaneously hypertensive rats compared with normal rats (Kawada et al, 2011). This resulted in attenuation of the AP reduction in the steady-state in response to step increases of CSP ( Figure 7c; (Bogaard et al, 2010;Chen et al, 2013;da Silva Gonçalves Bós et al, 2018). Monocrotaline decreased the dynamic gain of the baroreflex total arc at 0.01 Hz (Figure 7b; Table 2) by >55% compared with CTL rats, without changes in the corner frequencies.…”
Section: Baroreflex Dynamic Total Arc Functionmentioning
confidence: 89%
See 1 more Smart Citation
“…; Da Silva Gonçalves Bós et al . ). Our group, for example, reported reduced HRR in patients with pulmonary arterial hypertension (PAH), which independently predicted all‐cause mortality (Ramos et al .…”
Section: Introductionmentioning
confidence: 97%
“…Parasympathetic activity is suppressed, whereas the sympathetic nervous system is upregulated. [1][2][3] Increased sympathetic activity is associated with clinical deterioration and mortality, which may cause further compromise RV function. [3][4][5] Consequently, therapies that restore autonomic balance by inhibiting sympathetic activity, such as beta-blocker therapy, have been of interest for the past decades.…”
Section: Introductionmentioning
confidence: 99%